Birds, Birds, Birds: Co-Worker Similarity, Workplace Diversity and Job Switches - Boris Hirsch; Elke J. Jahn; Thomas Zwick (British Journal of Industrial Relations, 2019)
We investigate how the demographic composition of the workforce along the sex, nationality, education, age and tenure dimensions affects job switches. Fitting duration models for workers' job-to-job turnover rate that control for workplace fixed effects in a representative sample of large manufacturing plants in Germany during 1975–2016, we find that larger co-worker similarity in all five dimensions substantially depresses job-to-job moves, whereas workplace diversity is of limited importance. In line with conventional wisdom, which has that birds of a feather flock together, our interpretation of the results is that workers prefer having co-workers of their kind and place less value on diverse workplaces.
Keywords: 330